Agronomic and compositional assessment of genetically modified DP23211 maize for corn rootworm control. Issue 4 (1st October 2020) - Anderson, Jennifer A.; Mickelson, James; Challender, Mary; Moellring, Emily; Sult, Theresa; TeRonde, Sarah; Walker, Carl; Wang, Yiwei; Maxwell, Carl A.
ABSTRACT: DP23211 maize was genetically modified (GM) to express DvSSJ1 double-stranded RNA and the IPD072Aa protein for control of corn rootworm ( Diabrotica spp.). DP23211 maize also expresses the phosphinothricin acetyltransferase (PAT) protein for tolerance to glufosinate herbicide, and the phosphomannose isomerase (PMI) protein that was used as a selectable marker. A multi-location field trial was conducted during the 2018 growing season at 12 sites selected to be representative of the major maize-growing regions of the U.S. and Canada. Standard agronomic endpoints as well as compositional analytes from grain and forage (e.g., proximates, fibers, minerals, amino acids, fatty acids, vitamins, anti-nutrients, secondary metabolites) were evaluated and compared to non-GM near-isoline control maize (control maize) and non-GM commercial maize (reference maize). A small number of agronomic endpoints were statistically significant compared to the control maize, but were not considered to be biologically relevant when adjusted using the false discovery rate method (FDR) or when compared to the range of natural variation established from in-study reference maize. A small number of composition analytes were statistically significant compared to the control maize. These analytes were not statistically significant when adjusted using FDR, and all analyte values fell within the range of natural variation established from in-study reference range, literature range or tolerance interval, indicating that the composition of DP23211 maize grain and forage is substantially equivalent to conventional maize represented by non-GM near-isoline control maize and non-GM commercial maize.